2019
DOI: 10.1016/j.apnu.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Associations between schizotypal traits and antisocial behaviours in a sub-Saharan sample

Abstract: Schizophrenic symptoms have often been associated with antisocial behaviours (ASBs). Most studies have focused on violence. The association between schizophrenia and violence is often confounded by socio demographic characteristics of patients. Overemphasis on diagnosis, rather than traits, and the traditional focus on violence may have obscured associations between psychotic features and antisocial behaviour. In this study, an analogue sample (n = 604, females = 54.4%, mean age = 21. 46, SD = 5.89) completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…This might also be responsible for locking them indoors and being secretive about having a relative with schizophrenia [ 17 ]. According to Orjiakor and colleagues, societal behaviour towards individuals with schizophrenia causes challenges with social interpretation and violence in Sub-Saharan Africa, which constitutes another burden [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This might also be responsible for locking them indoors and being secretive about having a relative with schizophrenia [ 17 ]. According to Orjiakor and colleagues, societal behaviour towards individuals with schizophrenia causes challenges with social interpretation and violence in Sub-Saharan Africa, which constitutes another burden [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that individuals with schizophrenia and their families have little or no chance of getting married and procreating in Sub-Saharan Africa. According to Orjiakor and colleagues, societal behaviour towards individuals with schizophrenia causes challenges with social interpretation and violence in Sub-Saharan Africa, which in turn constitutes another burden 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Schizotypy, as well as con rmed schizophrenia, have been linked to aggressive behavior. For example, Orjiakor et al [11] found that schizotypal traits such as impulsive non-conformity were associated with physical and socially aggressive behavior in young adults. Several studies also indicated that schizotypy was independently associated with increased reactive aggression in children and adolescents [12][13][14].…”
mentioning
confidence: 99%